Understanding E-Loyalty in Gen Z Digital Banking Users: An Analysis of E-Service Quality, E-Trust, and E-Satisfaction - Dessyta Miranda Syaharani; Basuki, Ananto (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to identify the effects of e-service quality and e-trust on the e-loyalty of Gen Z users of Blu by BCA in Malang City with e-satisfaction as the mediating variable. This explanatory research elucidates the relationships between the dependent, independent, and mediating variables. Using non-probability sampling method and purposive sampling technique, 100 people considered as Gen Z (born between 1997 and 2012) who live in Malang City and use Blu by BCA were selected as the respondents. The data was harvested via online questionnaires and examined through path analysis in IBM SPSS 21, while the mediation test was performed using Sobel test. This study finds that e-service quality and e-trust directly have positive and significant impact on e-loyalty, that e-service quality and e-trust positively and significantly affect e-satisfaction, that e-service quality indirectly influences e-loyalty through the mediation of e-satisfaction, and that e-trust indirectly influences e-loyalty with the mediation of e-satisfaction.